2003
DOI: 10.1017/s0022112003004373
|View full text |Cite
|
Sign up to set email alerts
|

Thermocapillary suppression of the PlateauRayleigh instability: a model for long encapsulated liquid zones

Abstract: A cylindrical liquid bridge is unstable when its length is longer than its circumference, the Plateau–Rayleigh limit. This capillary instability is modified by fluid motions adjacent to the interface, which can be induced by thermocapillary stress, among other means. A simple flow model with symmetry that mimics the situation in encapsulated floating zones is analysed. The interfacial balance equation is formulated as a bifurcation problem, appropriate when the flows are nearly rectilinear. This balance captur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Xu and Davis [21] have studied the stability of long axisymmetric liquid zones subjected to axial temperature gradients which induce steady flows driven by thermocapillarity. Chen et al [22] have studied the effect of thermocapillarity on the Plateau-Rayleigh instability of a cylindrical liquid bridge. It has been shown that the thermocapillarity induced by axial temperature gradients has a stabilizing effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Xu and Davis [21] have studied the stability of long axisymmetric liquid zones subjected to axial temperature gradients which induce steady flows driven by thermocapillarity. Chen et al [22] have studied the effect of thermocapillarity on the Plateau-Rayleigh instability of a cylindrical liquid bridge. It has been shown that the thermocapillarity induced by axial temperature gradients has a stabilizing effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [22] have studied the effect of thermocapillarity on the Plateau-Rayleigh instability of a cylindrical liquid bridge. It has been shown that the thermocapillarity induced by axial temperature gradients has a stabilizing effect [21,22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of a liquid filament is then a mandatory preliminary step for producing a droplet (Chen et al 2003). This procedure is widely applied in flow-focusing devices.…”
Section: Introductionmentioning
confidence: 99%
“…Then many researchers obtained some asymptotic solutions of thermocapillary convection in encapsulated liquid bridge at low Ma number. [13][14][15][16] The influence of various factors on thermocapillary convection is also analyzed. Meanwhile, Li et al 17 and Prakash et al 18 analyzed the stability of thermocapillary convection in encapsulated liquid bridge using the analysis method of the linear stability and got the critical Ma numbers under various conditions.…”
Section: Introductionmentioning
confidence: 99%